Imatinib trough plasma levels do not correlate with the response to therapy in patients with chronic myeloid leukemia in routine clinical setting - Faber, Edgar; Friedecký, David; Mičová, Kateřina; Rožmanová, Sárka; Divoká, Martina; Jarošová, Marie; Indrák, Karel; Adam, Tomáš (Annals of hematology, 2012)
Association of trough imatinib plasma levels (IPL) with cytogenetic or molecular response to treatment in patients with chronic myeloid leukemia (CML) was repeatedly reported. We analyzed their value in the routine clinical setting in 131 patients with chronic phase CML in whom imatinib was applied as first- or second-line treatment. A total of 1,118 measurements were obtained by ultra-performance liquid chromatography-tandem mass spectrometry assay in patients treated with daily dose of imatinib ranging from 100 to 800 mg. Samples were obtained from 1 to 96 h after drug ingestion. High inter (36%) and intraindividual variability (9-33%) of IPL was observed. For analysis of correlation of IPL with treatment response, two sets of samples were selected according to the European LeukemiaNet (ELN) criteria. The first set consisted of 241 samples taken 24 ± 2 h after dosing in 54 patients, and the second one consisted of 329 samples taken 24 ± 4 h after imatinib ingestion in 84 patients. In both sets, only patients treated with 400 mg imatinib once daily for at least 18 months were included. From multiple measurements in individual patients, mean IPL were used. In both sets, we were not able to demonstrate a statistically significant correlation between IPL and response to treatment according to the ELN. We believe that this was due to the differences in patients' compliance, leukemia biology, and other variables that are difficult to eliminate in the routine clinical practice. The use of IPL for prognostic estimation in CML treatment outside the clinical trials is probably limited.
Keywords: dospělí; Diagnostic Tests, Routine; klinické laboratorní techniky; Female; pyrimidiny; Clinical Laboratory Techniques; Blood Chemical Analysis; Adult; výsledek terapie; ženské pohlaví; piperaziny; mladý dospělý; Predictive Value of Tests; prediktivní hodnota testů; lidé; chronická myeloidní leukemie; Antineoplastic Agents; protinádorové látky; biochemická analýza krve; Treatment Outcome; diagnostické testy rutinní; Aged, 80 and over; prognóza; retrospektivní studie; Benzamides; imatinib mesylát; biomarkery farmakologické; Male; Aged; benzamidy; Piperazines; Young Adult; Biomarkers, Pharmacological; Prognosis; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Retrospective Studies; Middle Aged; Imatinib Mesylate; Pyrimidines; Humans